Peningkatan Kualitas Produk Kunyit Asam Instan Produksi Kober Nurul Huda: Quality Improvement of Kunyit Asam Instant Drink Manufactured by Kober Nurul Huda - Syamsudin, Raden Aldizal Mahendra Rizkio; Sriarumtias, Framesti Frisma; Kurniawan, Deri Alan; Martiani, Isye (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Kober Nurul Huda was an early childhood education institution located at the foot of Mount Cikuray, in Dangiang Village, Garut Regency, West Java. To support the institution's economy, an innovation was needed to generate additional income, one of which was through the utilization of local plants into products. Turmeric was a plant that could be processed into various products, one of which was the traditional turmeric tamarind drink. The method used in this community service activity was a participatory approach through observation, training, assistance, and evaluation of the results. Training and assistance were provided to improve the quality of instant turmeric tamarind products. A questionnaire was given to 26 respondents, consisting of pre and post-tests, to assess participants' knowledge. A 33% increase in understanding was achieved. Furthermore, assistance was provided in packaging and product licensing. Attractive product packaging was developed, and an SPP-IRT certificate was obtained. Overall, the partners were satisfied with this activity.